Active integrins regulate white adipose tissue insulin sensitivity and brown fat thermogenesis - Francisco Javier Ruiz-Ojeda; Jiefu Wang; Theresa Bäcker; Martin Krueger; Samira Zamani; Simon Rosowski; Tim Gruber; Yasuhiro Onogi; Annette Feuchtinger; Tim J. Schulz; Reinhard Fässler; Timo D. Müller; et al. (Elsevier, 2021)
Objective: Reorganization of the extracellular matrix is a prerequisite for healthy adipose tissue expansion, whereas fibrosis is a key feature of adipose dysfunction and inflammation. However, very little is known about the direct effects of impaired cell-matrix interaction in adipocyte function and insulin sensitivity. The objective of this study was to determine whether integrin activity can regulate insulin sensitivity in adipocytes and thereby systemic metabolism. Methods: We characterized integrin activity in adipose tissue and its consequences on whole-body metabolism using adipose-selective deletion of β1 integrin (Itgb1adipo-cre) and Kindlin-2 (Kind2adipo-cre) in mice. Results: We demonstrate that integrin signaling regulates white adipocyte insulin action and systemic metabolism. Consequently, loss of adipose integrin activity, similar to loss of adipose insulin receptors, results in a lipodystrophy-like phenotype and systemic insulin resistance. However, brown adipose tissue of Kind2adipo-cre and Itgb1adipo-cre mice is chronically hyperactivated and has increased substrate delivery, reduced endothelial basement membrane thickness, and increased endothelial vesicular transport. Conclusions: Thus, we establish integrin-extracellular matrix interactions as key regulators of white and brown adipose tissue function and whole-body metabolism.